Analysis of the Influence of Financial Literacy and Financial Inclusion on Use of Financial Technology (Fintech) (Case Study of Islamic Bank Customers ) - Muhammad Aldrian Oktofa; Tuti Anggraini (Jurnal Ilmiah Ekonomi Islam, 2025)
This research is motivated by the rapid development technology digital finance ( financial technology or fintech ) which also change behavior customers in accessing and utilizing service finance , including in the sector Islamic banking . However , the high fintech adoption doesn't always work along with level literacy and inclusion finance society , especially Islamic bank customers who have characteristics and preferences special based on Sharia principles . Formulation The problem in this research is focused on the question : (1) What is the influence of financial literacy to use of fintech by sharia bank customers ? (2) How is the influence financial inclusion to use of fintech by Islamic bank customers ? and (3) What are financial literacy and financial inclusion? in a way simultaneous influential significant to use of fintech by sharia bank customers ? The purpose of This research is to analyze in a way in-depth how the level literacy finance and inclusion finance influence pattern use fintech services by Islamic bank customers , as well as to identify connection simultaneous between​ second variables independent the to variables dependent . This study uses approach qualitative with method studies bibliography and descriptive-analytical , which examines various primary and secondary sources , including research results previous studies , scientific journals , and academic books relevant . Research result shows that good financial literacy and financial inclusion own influence positive and significant to the use of fintech by sharia bank customers is good in a way partial and simultaneous . Literacy level adequate finances​ help customers understand risks and benefits fintech services , as well as making decisions smart finance . Meanwhile​ that , level inclusion good finances​ open wider access​ to products and services finance digital- based . Combination both of them push improvement optimal adoption of fintech in the context Islamic banking , in line with findings study previously stated that the ability individuals in understanding information finance as well as access to institution finance are two factors crucial in acceleration transformation digital finance .